Efficacy of diode laser application versus silver diamine fluoride (SDF) as a modification of Hall technique in primary teeth - Ghada A. Salem; Rasha F. Sharaf; Maryam El Mansy (Elsevier, 2022)
Background: The Hall technique is a new technique aimed at depriving bacteria of any substrate, thereby limiting the progression of caries. Silver diamine fluoride (SDF) and diode laser are documented to have an antibacterial effect on carious enamel and dentin by eradicating bacteria such as Streptococcus mutans. Aim: The current study aimed to increase the success rate of the Hall technique in carious primary molars by eradicating bacteria present in carious lesions using SDF or diode laser in combination with the Hall technique. Materials and methods: A total of 159 children aged 4-8 years were randomly divided into three equal groups: Group I, application of the Hall technique; Group II, SDF with Hall technique; Group III, diode laser with Hall technique. Children were recalled at regular intervals over a year. Results: At the end of the follow-up period, Group III showed the highest clinical success rate (94.3 %), followed by Group II (96.2 %), while Group I showed the lowest clinical and radiographic success rates (88.7 % and 86.8 %, respectively); however, these differences were statistically non-significant. Conclusion: Treatment of carious lesions using SDF or Diode Laser increased the success rate of the Hall technique in primary teeth.